Peran Association of South East Asian Nation (ASEAN) dalam Mengatasi Transnational Human Trafficking di Asia Tenggara - Pentury, Zachary Ivander; Waas, Richard Marsilio; Daties, Dyah Ridhul Airin (Faculty of Law, Universitas Pattimura, 2024)
Introduction: ASEAN, as a regional organization in Southeast Asia, aims to maintain security and stability in the ASEAN region, including addressing human trafficking.Purposes of the Research: The purpose of this study is to analyze and understand ASEAN's role in handling Transnational Human Trafficking in Southeast Asia.Methods of the Research: This study uses a normative juridical method with primary, secondary, and tertiary legal materials.Results of the Research: The research findings indicate that ASEAN has institutions such as SOMTC and ASEAN-ACT, and legal instruments such as the ASEAN Declaration Against Human Trafficking in Persons, Particularly Women and Children, APA, and ACTIP. Despite the principle of non-intervention, which can be a hindrance in some aspects of addressing human trafficking, ASEAN, through these institutions and mechanisms, has carried out its role and responsibility to maintain the stability of the Southeast Asian region